19.4k views
3 votes
(X^2+y^2+x)dx+xydy=0
Solve for general solution

1 Answer

4 votes

Check if the equation is exact, which happens for ODEs of the form


M(x,y)\,\mathrm dx+N(x,y)\,\mathrm dy=0

if
(\partial M)/(\partial y)=(\partial N)/(\partial x).

We have


M(x,y)=x^2+y^2+x\implies(\partial M)/(\partial y)=2y


N(x,y)=xy\implies(\partial N)/(\partial x)=y

so the ODE is not quite exact, but we can find an integrating factor
\mu(x,y) so that


\mu(x,y)M(x,y)\,\mathrm dx+\mu(x,y)N(x,y)\,\mathrm dy=0

is exact, which would require


(\partial(\mu M))/(\partial y)=(\partial(\mu N))/(\partial x)\implies (\partial\mu)/(\partial y)M+\mu(\partial M)/(\partial y)=(\partial\mu)/(\partial x)N+\mu(\partial N)/(\partial x)


\implies\mu\left((\partial N)/(\partial x)-(\partial M)/(\partial y)\right)=M(\partial\mu)/(\partial y)-N(\partial\mu)/(\partial x)

Notice that


(\partial N)/(\partial x)-(\partial M)/(\partial y)=y-2y=-y

is independent of x, and dividing this by
N(x,y)=xy gives an expression independent of y. If we assume
\mu=\mu(x) is a function of x alone, then
(\partial\mu)/(\partial y)=0, and the partial differential equation above gives


-\mu y=-xy(\mathrm d\mu)/(\mathrm dx)

which is separable and we can solve for
\mu easily.


-\mu=-x(\mathrm d\mu)/(\mathrm dx)


\frac{\mathrm d\mu}\mu=\frac{\mathrm dx}x


\ln|\mu|=\ln|x|


\implies \mu=x

So, multiply the original ODE by x on both sides:


(x^3+xy^2+x^2)\,\mathrm dx+x^2y\,\mathrm dy=0

Now


(\partial(x^3+xy^2+x^2))/(\partial y)=2xy


(\partial(x^2y))/(\partial x)=2xy

so the modified ODE is exact.

Now we look for a solution of the form
F(x,y)=C, with differential


\mathrm dF=(\partial F)/(\partial x)\,\mathrm dx+(\partial F)/(\partial y)\,\mathrm dy=0

The solution F satisfies


(\partial F)/(\partial x)=x^3+xy^2+x^2


(\partial F)/(\partial y)=x^2y

Integrating both sides of the first equation with respect to x gives


F(x,y)=\frac{x^4}4+\frac{x^2y^2}2+\frac{x^3}3+f(y)

Differentiating both sides with respect to y gives


(\partial F)/(\partial y)=x^2y+(\mathrm df)/(\mathrm dy)=x^2y


\implies(\mathrm df)/(\mathrm dy)=0\implies f(y)=C

So the solution to the ODE is


F(x,y)=C\iff \frac{x^4}4+\frac{x^2y^2}2+\frac{x^3}3+C=C


\implies\boxed{\frac{x^4}4+\frac{x^2y^2}2+\frac{x^3}3=C}

User Paulin Trognon
by
5.8k points